Social leadership and authority in the field of national and military security: problems of formation in the digital world - M. M. Kibakin (Цифровая социология)
The article reveals the author’s approach to the content of social leadership in the context of the development of a digital society at various levels – societal, institutional and concrete social. The author analyses the correlation between the concepts of “social leadership” and authority in the sphere of national and military security. Based on the author’s sociological research, the paper analyses the self-assessment of young people of their leadership qualities, authority and social influence on other people in accord- ance with their status in social networks. The study describes the social types based on the model of leadership and integration into the Russian civilizational space, the values of the Russian society. The paper substantiates the proposals to take into account the leadership qualities of social network administrators, moderators of information flows in the formation of the human potential of specialists in the development of digital platforms and global Internet content in the Russian segment of the virtual space, as well as the establishment of partnerships between national and military security actors and business structures of the digital economy, software developers, producers of Internet content. Separately, the author highlights the conditions for the formation of leadership positions of subjects of information and analytical work based on digital technologies to ensure national and military security. The study presents the author`s justification of the levels and content of digital information and analytical competencies of personnel in the system of ensuring national and military security, which will allow Russia to ensure technological social leadership in this area. The article reveals practical methods of organizing the educational process for training specialists in the field of digital information and analytical technologies, the possibility of using virtual educational means of training and control, Internet resources, and improving the security of the educational process in military educational organizations from negative hostile influences.